Safety and Effectiveness of Vessel Sealing for Dissection during Pancreaticoduodenectomy. Issue 3 (March 2013) - Pointer, David T.; Slakey, Lauren M.; Slakey, Douglas P.
Traditional pancreaticoduodenectomy dissection techniques are tedious and time-consuming. The LigaSure® Vessel Sealing System is an alternative to standard dissection methods. LigaSure® can be used in replace of ligatures, clips, and sutures in most of the pancreaticoduodenectomy procedure. The objective of this study was to examine our experience with LigaSure® in pancreaticoduodenectomies and to show the safety and time-effectiveness. Forty-three pancreaticoduodenectomies were performed by a single surgeon using the LigaSure® device in place of traditional dissection techniques. A retrospective chart review was conducted to evaluate patient management and outcome. Demographics, preoperative, intraoperative, and postoperative data were analyzed. The average patient age was 61 years. Primary pathologic diagnoses were: periampullary carcinoma (56%), chronic pancreatitis (5%), cystic lesion (26%), neuroendocrine tumor (7%), and other (5%). Our patient population demonstrated American Society of Anesthesiologists Class I (2%), Class II (14%), III (75%), and IV (9%). Average operative time was 4:11 hours. The study group required an average of 0.49 ± 1.35 units of blood. Eight patients (19%) received blood transfusion, receiving an average of 2.63 ± 2.13 units. Patients had a median hospital stay of 10 days (range, 5 to 41 days). An oral diet was ordered for most patients by Day 4. Fourteen patients (32.5%) had a complication, including two patients requiring additional surgery for drainage of abscess. There were no postoperative deaths. The use of LigaSure® is a practical and safe alternative to standard dissection techniques. Operative time, blood loss, and complication rate are favorable compared with published series.